Prevalence of dementia and its associated risk factors among elderly patient attending Outpatient Department of a tertiary care hospital in Lucknow - Kumari, Rashmi; Singh, Arvind Kumar; Kaushik , Amit; Thakker, Tanya; Singh, Shikhar; Kandpal, Sunil Dutt (Indian Journal of Community Health, 2021)
Background: Dementia is a broad category of brain diseases that causes a chronic, progressive and gradual decrease in cognitive function i.e. ability to think and remember that is great enough to affect a person’s daily functioning beyond what might be expected from normal ageing. According to American Psychiatric Association, “Dementia is a syndrome caused by a variety of brain illnesses that affect memory, thinking, behaviour and the ability to perform everyday activities”. Aim & Objectives: To assess the prevalence of dementia among the patients above 60 years of age attending the outpatient department of Tertiary care super specialty hospital. To assess the risk factors associated with occurrence of dementia in patients attending outpatient department of Tertiary care super specialty hospital. Settings and Design: Study design: - Cross-sectional observational study. Study area: - Tertiary care super-specialty hospital. Study setting: - Outpatient department (OPD)of Tertiary care super specialty hospital. Methods and Material: Study population: - Patients above 60 years of age and attending Outpatient Department of the tertiary care super specialty hospital. Duration of Study: - 4 months. Sample size:- 223 elderly participants from the registration counter of the Outpatient Department of tertiary care hospital. Statistical analysis used: Data was analysed using SPSS, version 24.0. Univariate Logistic Regression, Multivariate Logistic Regression, Odds Ratio. Results: The study was conducted on a total of 223 patients out of which only 210 patients completed the questionnaire and matched our criteria. Thus, 210 patients are analysed for the result. In our study which included the patients above 60 years of age out of which the maximum participants (52.4%) were of age group 65-75. In our study 66.2% participants had normal cognitive functioning while 33.8% of total participants were found to have dementia. Out of these 33.8% participants having impaired cognitive functioning, 13.8% and 20% had severe and borderline dementia respectively. Dementia was found to be more common in females. Conclusions: Statistically significant association of dementia has been found with female gender, rural residence, joint family and a greater number of family members, poor education, pan masala consumption, daytime drowsiness, and problem in sleep pattern, social intolerance and frequent fights.